PENINGKATAN LITERASI BERBAHASA INGGRIS MELALUI READING ALOUD PADA SISWA SEKOLAH DASAR - S.Pd., M.Pd, Fitri Nurdianingsih; Muchyidin, M. Syaichul; Matin, Moh. Fuadul; Falah, Sabila Nur (Penerbit LPPM- STKIP PGRI Bangkalan, 2023)
The objective of this community service is to improve the English skill literacy of the elementary school students. This activities were done by some lecturers and also college students. There were 14 students which divided into 4th and 5th grade of students at SDN Bulu Bojonegoro. This community service implemented read aloud method using bilingual story book in order to help the students more familiar with English. The result from this community service is the students more interested when the educators reading aloud the story book, so they can apply the vocabulary and pronounce the right vocabulary in English